2018
DOI: 10.1177/1535370218794418
|View full text |Cite
|
Sign up to set email alerts
|

Detection and interpretation of fecal host mRNA in rural Malawian infants aged 6–12 months at risk for environmental enteric dysfunction

Abstract: Recent studies have suggested that environmental enteric dysfunction can be assessed in rural African children by measuring levels of fecal mRNA transcripts. The field collection of fecal samples is less invasive and cumbersome than administration of the lactulose:mannitol test, which is typically used to assess environmental enteric dysfunction. This study sought to determine if, as in children aged 12-60 months, an array of seven fecal host transcripts (CD53, CDX1, HLA-DRA, TNF, S100A8, MUC12, and REG1A) cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 19 publications
3
8
0
Order By: Relevance
“…Our study adds to the growing body of literature on field appropriate biomarkers of EED. The clusters of host fecal mRNA transcripts identified by this study have also been reported previously ( 31 ). Agreement between the clusters of inflammation and permeability with other more established EED biomarkers gives us confidence that they are measuring changes to the intestine characteristic of EED.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our study adds to the growing body of literature on field appropriate biomarkers of EED. The clusters of host fecal mRNA transcripts identified by this study have also been reported previously ( 31 ). Agreement between the clusters of inflammation and permeability with other more established EED biomarkers gives us confidence that they are measuring changes to the intestine characteristic of EED.…”
Section: Discussionsupporting
confidence: 86%
“…Although the biomarkers in our study did not all agree with each other, this may be a sign that they are measuring different aspects and stages of the complex condition that is EED. Similar to our findings, other studies have found conflicting results for associations between the biomarkers examined in this study ( 11 , 18 , 31 ). Differences in age, study design, and selection of biomarkers among studies muddy the evidence for the association between EED and growth outcomes.…”
Section: Discussionsupporting
confidence: 82%
“…There is no agreed case definition for EED. Differential urinary excretion of two sugars, typically lactulose and mannitol, has most often been used to characterize abnormalities in gut permeability and absorption, but this test has substantial limitations [17,18] and only captures part of the pathology underlying EED [15]. To date, studies have failed to demonstrate reproducible changes in these markers following interventions.…”
mentioning
confidence: 99%
“…More recent studies have used fluorescein as a marker of the leakiness of the mucosa, either by showing leakage of fluorescein from the systemic circulation into the gut lumen during endoscopy (52,58) , or by showing leakage of oral fluorescein into the systemic circulation (59,60) . In an ingenious approach, transcriptomic analysis of shed enterocytes in stool samples identified mucin and inflammatory genes associated with EE in an entirely non-invasive way (61) .…”
Section: Mucosal Abnormalities In Environmental Enteropathymentioning
confidence: 99%